Anticancer and Antitumor Potential of Fucoidan and Fucoxanthin, Two Main Metabolites Isolated from Brown Algae - Soheil Zorofchian Moghadamtousi; Hamed Karimian; Ramin Khanabdali; Mahboubeh Razavi; Mohammad Firoozinia; Keivan Zandi; Habsah Abdul Kadir (The Scientific World Journal)
Seaweed is one of the largest producers of biomass in marine environment and is a rich arsenal of active metabolites and functional ingredients with valuable beneficial health effects. Being a staple part of Asian cuisine, investigations on the crude extracts of Phaeophyceae or brown algae revealed marked antitumor activity, eliciting a variety of research to determine the active ingredients involved in this potential. The sulfated polysaccharide of fucoidan and carotenoid of fucoxanthin were found to be the most important active metabolites of brown algae as potential chemotherapeutic or chemopreventive agents. This review strives to provide detailed account of all current knowledge on the anticancer and antitumor activity of fucoidan and fucoxanthin as the two major metabolites isolated from brown algae.